Ecological Reconstruction of Rain-source Rivers after Sewage Interception in Highly Intensive Development Areas — A Case Study of Longgang River in Shenzhen - CHEN Yu; YANG Xiuchun; WANG Cong; XU Shengjun; WANG Jinglin (Renmin Zhujiang)
The Longgang River in Shenzhen is a representative of the rain-source rivers in highly intensive open areas.In recent years,Shenzhen has carried out sewage interception reconstruction along the Longgang River Basin.Although the water quality of the basin was improved,the reconstruction of the river's ecosystem has been neglected,resulting in spatially discontinuous transverse and longitudinal sections,damaged biological habitats,and a degraded biological community structure.A technology system for combined ecological river reconstruction is developed to provide technical support for the reconstruction of rain-source rivers featuring natural channel imitation,restoration of aquatic habitats,and ecological construction of riverside landscape corridors.The overall idea and technical framework of ecological reconstruction proposed in this paper can fully support the construction of a comprehensive demonstration zone for the reconstruction of aquatic ecological and healthy habitats in Shenzhen.Specifically,substantial increases are achieved in the species and diversity of aquatic organisms in the Longgang River Basin (an increase of 82.7% in species abundance and one of 46.5% in the diversity index),with intolerant species of benthic animals observed and the number of indigenous fish increased.The research results provide engineering samples for the ecological reconstruction of rain-source rivers in highly intensive development areas.